The Dynamic Relationship Between Investments in Brand Equity and Firm Profitability: Evidence Using Trademark Registrations - Dirk Crass; Dirk Czarnitzki; Andrew A. Toole (International Journal of the Economics of Business, 2019)
Most marketing practitioners and scholars agree that marketing assets such as brand equity significantly contribute to a firm's financial performance. In this paper, we model brand equity as an unobservable stock that results from up to 30~years of past brand-related investment flows. Using firm-specific trademarks as investment proxies, our results show a significant long-run impact on financial performance. The dynamic profile of brand-related investments has an inverted-U shape that reaches its peak after 11~years. On average, it takes four years before brand-related investments show a positive return, and investments older than 19~years show no significant impact. For the median trademarking firm, brand equity contributes exteuro265,000 to annual profits.
Keywords: O31; O34; 330; Brand Equity; Firm Profitability; Intellectual Property Rights; Trademarks